Potential contribution of cereal and milk based fermented foods to dietary nutrient intake of 1-5 years old children in Central province in Zambia - Chileshe, Justin; Talsma, Elise F.; Schoustra, Sijmen; Borgonjen-van den Berg, Karin J.; Handema, Ray; Zwaan, Bas J.; Brouwer, Inge D. (Public Library of Science, 2020)
Zambia is still facing undernutrition and micronutrient deficiencies despite fortification and supplementation programmes stressing the need for additional solutions. Fermented foods have the potential to improve nutrient intake and, therefore, could have an important role in food based recommendations (FBRs) to ensure adequate intake of nutrients for optimal health of populations. Secondary dietary intake data was used in Optifood, a linear programming software to develop FBRs, for children aged 1–3 and 4–5 years in Mkushi district of Zambia. Three scenarios per age group were modeled to determine FBRs based on: (1) FBRs based on local available foods (2) FBR and Mabisi, a fermented milk beverage, and (3) FBR with Munkoyo, a cereal fermented beverage. The scenarios were compared to assess whether addition of Mabisi or Munkoyo achieved a better nutrient intake. FBRs based on only locally available non-fermented foods did not meet ≥70% of recommended nutrient intake (RNI) for calcium, fat, iron and zinc, so-called problem nutrients. The addition of Munkoyo to the FBRs did not reduce the number of problem nutrients, but after adding Mabisi to the FBR’s only iron (67% of RNI) in the 1–3 year age group and only zinc (67% of RNI) in the 4–5 year age group remained problem nutrients. Mabisi, a fermented milk product in combination with the local food pattern is a good additional source of nutrients for these age groups. However, additional nutrition sensitive and cost-effective measures would still be needed to improve nutrient intake, especially that of iron and zinc.